Hypothyroidism Induced Severe Rhabdomyolysis in a Hemodialysis Patient - Erhan Tatar; Tolgay Isikyakar; Kezban Pinar Yeniay; Hasan Huseyin Uzuner; Ebru Sevinc Ok (Case Reports in Medicine)
Hypothyroidism occurs relatively common and is a significant cause of morbidity and mortality during the course of chronic kidney disease. Rhabdomyolysis is a potentially life-threatening condition characterised by necrosis of muscular tissue and rarely associates with hypothyroidism. Here we describe a case of rhabdomyolysis due to severe hypothyroidism in a 56-year-old female hemodialysis patient.